Pengabdian Kepada Masyarakat Tentang Pentingnya Penggunaan Gawai Sebagai Media Belajar Pada Anak Usia Dini Di Masa Pandemi - Hilyah Ashoumi; Tholib Hariono (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
The purpose of socializing the role of using gadgets is a new understanding for parents regarding the role of using gadgets as learning media which is very much needed during the COVID-19 pandemic and the effects of government regulations related to the teaching and learning process that is required to be carried out online. This is important to implement because of problems with the An-Najah Tembelang PAUD educational institution which is not ready for the learning process during the pandemic. One of the problems that occurs is the lack of readiness of parents to independently accompany students at home, even though most of the parents are housewives who do not have other activities outside the home, from here it can be identified problems that occur not because of busy people. students' parents, but there is a lack of understanding of the use of learning media for parents. Steps in Mentoring through surveys to Konto Tembelang Jombang Village, Team visit to the Konto Tembelang Jombang Village area, Identification of problems and solutions offered, Determining solutions and designing community service activities, Implementation of community service activities, Evaluation of Program Implementation and Sustainability.